Sustainability of an ad-hoc coastal development : a case study on Karon Beach, Phuket. - Cheong, Hsi Min. (2008)
This study presents the case of an ad-hoc coastal development in Phuket, Thailand. Principles of sustainability are applied in analyzing the sustainability of the resort.